2014
DOI: 10.1002/term.1851
|View full text |Cite
|
Sign up to set email alerts
|

The role of osteoclasts in bone tissue engineering

Abstract: The success of scaffold-based bone regeneration approaches strongly depends on the performance of the biomaterial utilized. Within the efforts of regenerative medicine towards a restitutio ad integrum (i.e. complete reconstruction of a diseased tissue), scaffolds should be completely degraded within an adequate period of time. The degradation of synthetic bone substitute materials involves both chemical dissolution (physicochemical degradation) and resorption (cellular degradation by osteoclasts). Responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 174 publications
(183 reference statements)
1
108
0
2
Order By: Relevance
“…Bone regeneration is a complex process that involves the coordination of a variety of different cascades and can be typically characterised by four overlapping stages. Initial inflammatory response is followed by bone formation, vascularisation and bone remodelling [5][6][7]. One of the core limitations for bone healing of large defects is the inadequate vascularization of applied grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Bone regeneration is a complex process that involves the coordination of a variety of different cascades and can be typically characterised by four overlapping stages. Initial inflammatory response is followed by bone formation, vascularisation and bone remodelling [5][6][7]. One of the core limitations for bone healing of large defects is the inadequate vascularization of applied grafts.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the fact that bone has a healing capacity through bone remodeling in response to injury or tumor destruction, the limiting factor for regeneration is linked not only with the individual's age but also with the amount of bone loss or damage. Despite the possibility of using auto-, allo-or xenografts for bone replacement there are clinical risks including graft availability, infection, reduced mechanical movement, a poorly functioning graft or graft rejection [2]. Bone tissue engineering represents an alternative to current approaches with ultimate goal being the combination of progenitor cells with growth factors and biomaterial substrates to form a three-dimensional (3D) structure that supports new bone formation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bone tissue engineering represents an alternative to current approaches with ultimate goal being the combination of progenitor cells with growth factors and biomaterial substrates to form a three-dimensional (3D) structure that supports new bone formation [3][4][5]. An assortment of materials such as calcium carbonate, hydroxyapatite (HAp), bioactive glasses (BG) like 45S5 BG, tricalcium phosphate (TCP), biphasic ceramics of HAp and α-or β-TCP, biopolymers and numerous biodegradable polymer-ceramic composites are of great interest for the development of bone substitutes in bone repairing and reconstruction [2,6,7]. Nevertheless, bone regeneration is a complex process that involves the coordination of a variety of different cascades and can be typically characterized by initial inflammatory response, followed by bone formation, vascularization and bone remodeling [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that TRAP-positive osteoclastic cells have been seen on the surface of deproteinized.collagen This implies that collagen fibrils are resorbed not only enzymatically, but also phagocytically. This was the case of the non sintered DPHa [76]. Our study showed that most of the newly formed bone in the augmented sinus The grafting material is an important determinant of bone augmentation procedures being a success or a failure.…”
Section: Discussionmentioning
confidence: 62%